PENGEMBANGAN PEREKONOMIAN DESA DENGAN PEMANFAATAN POTENSI PERIKANAN MELALUI PELATIHAN PENGOLAHAN PRODUK PERIKANAN BAGI MASYARAKAT DESA DUNU, KECAMATAN MONANO KABUPATEN GORONTALO UTARA - Erlansyah; Reinal Putalan; Muhammad Rizq Gobel; Nisfa Daud Supu; Wila Rumina Nento; Meilinda Lestari Modjo; Krishna Anugrah; Sri Ariyanti Sabiku; Poppy Arnold Kadir; Rendy Wijaya; Yumanraya Noho (Jurnal Abdimas Terapan, 2024)
The utilization of fisheries' potential as a source of animal protein needs to be developed to maximize fisheries’ potential, especially in North Gorontalo Regency. In addition to adding economic value, fishery product processing provides a positive impact in the form of knowledge for coastal communities. Fishery product processing Fishery products, especially fish, can be processed into various products such as nuggets. Nuggets are processed food products from animal protein sources popular with small children and adults. This service activity aims to increase homemakers' knowledge about fish processing innovation through fish nugget processing in Dunu Village, Monano District, North Gorontalo. The implementation of activities is aimed at homemakers, and the method of service activities is participatory learning and action through counseling accompanied by making fish nuggets. The activity went smoothly and was enthusiastically followed by the participants. The results were increased knowledge and understanding of homemakers about diversifying fishery processing products, namely fish nuggets. This activity is expected to increase the added value of fishery products through the diversification of processed fishery products to increase the added value of fishery products.